1999
DOI: 10.1007/s100249900133
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Intraspinal Lipomas: Histological Analysis of 234 Cases and Review of the Literature

Abstract: The clinical, radiologic, and pathologic data from a series of 234 patients hospitalized in the Pediatric Neurosurgical Department of the Necker-Enfants Malades Hospital, Paris, for congenital intraspinal lipomas and operated on from 1976 to 1995 were examined. Histological studies showed that these lesions may be simple lipomas, similar to those developing elsewhere in the body, or they may be more complex forms including in addition to the lipomatous component a variety of unusual ectopic tissues of ectoderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 22 publications
1
34
0
1
Order By: Relevance
“…Second is the presence of associated malformations, especially lipomyelocele, lipoma and diastematomyelia [20]. Lipomas of the CM are more underdiagnosed than those of the filum [2,21]. Third is the appearance of the CM.…”
Section: Discussionmentioning
confidence: 99%
“…Second is the presence of associated malformations, especially lipomyelocele, lipoma and diastematomyelia [20]. Lipomas of the CM are more underdiagnosed than those of the filum [2,21]. Third is the appearance of the CM.…”
Section: Discussionmentioning
confidence: 99%
“…Dass sich bei dieser Patientin zwei intraspinale Lipome an unterschiedlichen Höhen im Rahmen von Diastematomyelien finden, ist ungewöhnlich und findet sich unseres Wissens nicht in der Literatur. Selbst in einer Analyse von 234 intraspinalen Lipomen durch Lellouch-Tubiana et al [7] wird ein mehrmaliges Auftreten von Lipomen nicht berichtet. Lipome sind darüber hinaus vor allem im Rahmen von Lipomyelomenigozelen, aber auch anderen dysraphischen Störungen wie dem Dermalsinus, der Fibrolipomatose, des Filum terminale und dem Split-Notochord-Syndrom vorzufinden [9].…”
Section: Diskussionunclassified
“…However, lipomas do not consist entirely of fibroadipose tissues. A variety of mesodermal tissues such as bony and cartilaginous tissues, as well as ectodermal and endodermal tissues, are also often observed DOI: 10.1159/000490391 [1,2]. It has been reported that, in 234 histological specimens of spinal lipomas, bone and cartilage was noted in 8 (3%) and 15 (6%), respectively [2].…”
Section: Introductionmentioning
confidence: 99%